Ethnic diversity and preferences for redistribution - Matz Dahlberg; Karin Edmark; Heléne Lundqvist (Uppsala University, Department of Economics, 2011)
If people are more altruistic towards their own kind, the increased ethnic heterogeneity resulting from increased immigration to Europe in recent decades will likely lead to reduced support for redistribution among natives. This paper exploits a nationwide program placing refugees in municipalities throughout Sweden during the period 1985-94 to isolate exogenous variation in immigrant shares and can thereby estimate causal effects of increased ethnic heterogeneity on preferences for redistribution, defined as preferred social benefitt levels as obtained from panel survey data on inhabitants of the receiving municipalities. The results show that a larger immigrant population leads to less support for redistribution, especially among respondents with high income and wealth. We also establish that OLS estimators that do not properly deal with endogeneity problems - as in earlier studies - are likely to yield positively biased effects of ethnic heterogeneity on preferences for redistribution.
urn:nbn:se:uu:diva-140797
Keywords: D31; D64; I3; Z13; 330; income redistribution; ethnic heterogeneity; immigration; Einkommensumverteilung; Präferenztheorie; Ethnische Beziehungen; Altruismus; Einwanderung; Schweden